2020
DOI: 10.1177/0309364620968644
|View full text |Cite
|
Sign up to set email alerts
|

Education in prosthetic and orthotic training

Abstract: There is a long history of prosthetic and orthotic services helping to mitigate the impact of physical impairment by restoring function, and enabling and equipping the user. The training of health professionals who design, fit, and maintain prosthetic and orthotic devices has evolved over the centuries, reflecting an increase in knowledge, technology, understanding, and social attitudes in each era. Improvements in pedagogical thinking and biomechanical understanding, as well as the advent of new integrated te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…This is in line with a study's finding that physical travel and cultural competencies improve the cross-cultural learning while demanding effort and social dynamics. 28,29 The study findings also demonstrated that the international service-learning programs are potentially beneficial to the development of intercultural competence by virtue of their immersive nature which facilitates the intercultural interaction; this is the fact that could not be replicated in classrooms and the formal curricular programs. 13 Service learning is also beneficial to students because many employers seek for generic competencies in employees including communication skills, attitude, team working, decision-making, and problem-solving skills, 27 and this was the item admitted by Hong Kong and American students during the group interviews.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This is in line with a study's finding that physical travel and cultural competencies improve the cross-cultural learning while demanding effort and social dynamics. 28,29 The study findings also demonstrated that the international service-learning programs are potentially beneficial to the development of intercultural competence by virtue of their immersive nature which facilitates the intercultural interaction; this is the fact that could not be replicated in classrooms and the formal curricular programs. 13 Service learning is also beneficial to students because many employers seek for generic competencies in employees including communication skills, attitude, team working, decision-making, and problem-solving skills, 27 and this was the item admitted by Hong Kong and American students during the group interviews.…”
Section: Discussionmentioning
confidence: 85%
“…This is in line with a study's finding that physical travel and cultural competencies improve the cross-cultural learning while demanding effort and social dynamics. 28,29 The study findings also demonstrated that the international service-learning programs are potentially beneficial to the development of intercultural competence by virtue of their immersive nature which facilitates the intercultural interaction; this is the fact that could not be replicated in classrooms and the formal curricular programs. 13…”
Section: Discussionmentioning
confidence: 87%
“…The decision to exclude these responses was due to the difference in clinical and technical work compared with more developed countries. 26-28…”
Section: Resultsmentioning
confidence: 99%
“…The decision to exclude these responses was due to the difference in clinical and technical work compared with more developed countries. [26][27][28] Across all respondents, 52% (n 5 119) were women. Mean length of employment as a prosthetist or orthotist was 2 years (SD 5 4.3) and mean weekly hours of work was 42.2 hours (SD 5 11.4).…”
Section: Participantsmentioning
confidence: 99%
“…Interdisciplinary collaboration is becoming increasingly important in the field of orthopedic prosthesis design [ 52 ]. By bringing together experts from various disciplines such as materials science, biomechanics, medicine, and engineering, it is possible to develop more effective solutions that address the complex challenges of orthopedic prosthesis design [ 53 ].…”
Section: Future Directions For Orthopedic Prosthesis Designmentioning
confidence: 99%